Trust and controlling - Bieńkowska Agnieszka; Zabłocka-Kluczka Anna (Management)
The purpose of this study is to discuss the trust within and towards an organisation in the context of implementation of controlling therein. In this context the essence of trust and its importance in organisation management was presented, as well as trust in the contemporary management methods and concepts. Controlling as a trust-building factor inside an organisation was pointed out. Especially controlling and control were described. Moreover management by considering deviations in controlling and the teamwork in controlling were described. The role of controlling in process of trust-building to an organisation was presented. Establishing relations with the environment and systems of measurement of organisation’s achievements were presented, too.